FAKTA SEJARAH DALAM NOVEL KINCIR WAKTU KARYA AKMAL NASERY BASRAL (KAJIAN NEW HISTORICISM) - Sri Wahyuni; Faika Burhan (Cakrawala Listra: Jurnal Kajian Sastra, Bahasa, dan Budaya Indonesia, 2023)
New Historicism is one of the studies that can be used to see historical facts in literary works. One of the literary works that contains historical facts in storytelling is the novel Kincir Waktu by Akmal Nasery Basral, so this research will discuss historical facts in the novel Kincir Waktu by Akmal Nasery Basral (New Historicism Study). This study aims to investigate the historical facts in the novel Kincir Waktu by Akmal Nasery Basral. This research will provide an overview of historical facts using the New Historicism theory. The research method used is descriptive qualitative which presents and decodes the data using words. The data in this study are in the form of text contained in Akmal Nasery Basral's novel Kincir Waktu which was gathered through several steps of reading and note-taking techniques to mark valuable parts in the narrative and dialogue of the characters. This analysis is used to find a picture of historical facts based on the study of New Historicism, namely sees literary works as social documentation that cannot be separated by politics, economics, and society. The results of this study show that the novel Kincir Waktu by Akmal Nasery Basral represents the May 1998 riots. In the novel there are historical facts consisting of three parts, namely ; (1) Sexual violence against Chinese women ; (2) Political interference in the 1998 humanitarian tragedy ; (3) Background to the May 1998 tragedy. Keywords: Novel Kincir Waktu, Historical Facts, New Historicism, Chinese Ethnicity